Proceedings of the American Mathematical Society. Volume 138, Number 2, 2010 - American Mathematical Society (American Mathematical Society, 2010)
The $q$-tangent and $q$-secant numbers via basic Eulerian polynomials Dominique Foata; Guo-Niu Han Proc. Amer. Math. Soc. 138 (2010), 385-393. Abstract, references and article information Retrieve article in: PDF MathSciNet review: 2557155